Whole-genome identification of HSF family genes in Cerasus humilis and expression analysis under high-temperature stress - Mu, Xiaopeng; Zhang, Jiating; Wang, Chenyi; Chen, Liming; Zhang, Jianying; Wang, Pengfei; Zhang, Jiancheng; Zhang, Bin; Du, Junjie (Frontiers in Plant Science, 2025)
The heat shock factors (HSFs) play important roles in activating heat stress responses in plants. Cerasus humilis (Ch) is a nutrient-rich fruit tree that can resist various abiotic and biotic stressors. However, the HSFs in C. humilis have not yet been characterized and their roles remain unclear. In this study, 21 ChHSF gene members were identified after searching the entire genome of C. humilis. Gene structure and motif composition analysis revealed that 16 ChHSF genes had only one intron and the motif3 was highly conserved in family of ChHSFs. Furthermore, the cis-acting elements analysis indicated that they most ChHSFs participate in plant growth and development, abiotic stress responses, and plant hormone regulations. By analyzing the tissue specific transcriptomes, it was found that most ChHSF genes had higher expression levels in leaves than in other tissues of C.humilis. Notably, the ChHSF04 gene exhibited a striking 115.5-, 14.4-, and 16.0-fold higher expression in leaves relative to seeds, roots, and fruits, respectively. The high temperature (40 °C) treated C. humilis seedlings quantitative real-time polymerase chain reaction (qRT-PCR) was conducted on all ChHSF gene members. The results show that the expression of most ChHSF genes in the leaves was significantly upregulated and peaked at 12 h under the heat stress and the expression levels of ChHSF04, ChHSF05, ChHSF12, ChHSF13, ChHSF15 and ChHSF16 exhibited 53-, 33-, 24-, 22-, 43- and 65-fold upregulation, indicating that these genes may play important roles in early response to heat stress in C. humilis. These results provide valuable insights into the evolutionary relationship of the ChHSF gene family and its role in high temperature stress responses.